Comparison of Efficacy of Angiotensin-Converting Enzyme Inhibitors (ACEIs) and Angiotensin Receptor Blockers (ARBs) in Delaying Diabetic Nephropathy - Tahir, Fraz; Rizvi, Syeda Arsheen; Akhtar, Faisal Naveed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effect of angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers on renal damage in terms of change in mean albumin-to-creatinine ratio.Study Design: Cross-sectional study.Study Place and Duration: PNS Hafeez, Islamabad, Pakistan, from Feb to Jul 2021.Methodology: We included 1300 patients using non-probability purposive sampling, divided into two groups. Patients aged between 30-60 years, suffering from Type 2 Diabetes Mellitus with detectable microalbuminuria having Urine Albumin to Creatinine Ratio >30mg/g, before starting the medication with either angiotensin‐converting enzyme inhibitors or ARB, were considered for inclusion. Patients with ischemic heart disease, vasculitis, glomerulonephritis, protein-losing enteropathy, liver disease, malignancy, urinary tract infection, and any contraindication of ACE inhibitor and ARBs were excluded.Results: In Group A, the duration of disease was 9.22±3.45 years, and in Group B, it was 9.11±3.58 years. The delay in nephropathy progression between the two groups was established by measuring the mean change in ACR after 3 months in both groups. It was established that angiotensin‐converting enzyme inhibitors (mean change 0.93±0.16 mg/g) was adequately efficient in delaying the albuminuria over three months of treatment than ARBS (mean change 1.097±0.26 mg/g) (p˂ .001).Conclusion: In comparison, angiotensin‐converting enzyme inhibitors were more adequate than angiotensin receptor blockers in creating change in mean albumin-to-creatinine ratio.